2003
DOI: 10.1093/jnci/95.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality-of-Life Measurement in Randomized Clinical Trials in Breast Cancer--Taking Stock

Abstract: Measurement of health-related quality-of-life (HRQOL) in randomized clinical trials in breast cancer has become common. In this review, we take stock of the contribution that HRQOL measurement in breast cancer clinical trials makes to clinical decision making regarding selection of optimal treatment. A series of MEDLINE searches was conducted to identify all randomized trials in breast cancer that included self-reported HRQOL or psychosocial outcomes. A total of 256 citations were identified that included HRQO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
13

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(156 citation statements)
references
References 77 publications
1
142
0
13
Order By: Relevance
“…These observations highlight the need for researchers to select instruments that address domains likely to be influenced by the interventions that have shown significant sensitivity in detecting small but clinically important changes. 26 Taken together, the current results provide strong evidence for a psychologic benefit for group support of various types in the setting of metastatic breast cancer. Questions that arise from these observations include whether all women (or only distressed women) benefit from such interventions and what should be the optimal duration of the intervention (long-term vs. short-term).…”
Section: Psychosocial Effects Of Group Interventions In Metastatic Brsupporting
confidence: 57%
“…These observations highlight the need for researchers to select instruments that address domains likely to be influenced by the interventions that have shown significant sensitivity in detecting small but clinically important changes. 26 Taken together, the current results provide strong evidence for a psychologic benefit for group support of various types in the setting of metastatic breast cancer. Questions that arise from these observations include whether all women (or only distressed women) benefit from such interventions and what should be the optimal duration of the intervention (long-term vs. short-term).…”
Section: Psychosocial Effects Of Group Interventions In Metastatic Brsupporting
confidence: 57%
“…A recent review of HRQL trials in breast carcinoma has found that HRQL assessments provide little contribution to clinical decision-making about treatment alternatives except in certain clinical situations (e.g., trials of treatment equivalency and trials with special HRQL end points). 21 It is currently not known whether this finding is similar for other cancer sites. For patients with esophageal carcinoma, HRQL measures may guide treatment decisions because of the magnitude of negative impact that potentially curative treatment has on HRQL and because survival benefits related to combination treatment are fairly small.…”
Section: Discussionmentioning
confidence: 90%
“…A systematic analysis of BC CTs concluded that the utility of HRQOL analyses depended on the setting, but in some scenarios provided added information for clinical decision-making beyond that of traditional medical outcomes [145]. For example, Table 5 Research recommendations and high priority studies in pharmacogenomics…”
Section: Hrqol and The Short-term Effects Of Therapymentioning
confidence: 99%
“…HRQOL measurement did not influence clinical decisionmaking in adjuvant therapy and provided little information beyond that obtained from traditional medical outcomes such as toxicity in metastatic trials. However, results of HRQOL questionnaires targeting specific symptoms (e.g., emesis) guided treatment decisions when evaluating symptom control and was the only measure in psychosocial intervention trials [145]. In order to address some of the challenges of measuring the outcomes and provide guidance regarding the settings in which they should be measured, efforts are underway to standardize effective patientreported outcomes (PRO).…”
Section: Target Accrual Study Population Research Questionsmentioning
confidence: 99%